Competition decreases with relatedness and lek size in mole crickets: a role for kin selection?. (7th June 2018) - Keane, Kit T; Booth, Warren; Howard, Daniel R; Golden, Timothy M J; Hill, Peggy S M
Abstract : Are "leks, " where males advertise in groups for females to gain mating opportunities, the result of competition, or cooperation? In the prairie mole cricket Gryllotalpa major, we present evidence that 1) males display near relatives and 2) males on smaller, more highly related leks experience lower levels of competition. These data suggest that kin selection may be operating within kin clusters on leks and males likely gain a reproductive benefit by displaying nearby relatives. Abstract: Twenty years ago, Kokko and Lindstrom (1996) introduced the hypothesis that kin selection may drive the evolution of leks, shifting the lek-paradigm away from a competitive framework and spurring research on the relatedness of males on leks. However, support for Kokko and Lindstrom's kin-selection hypothesis has been sparse; most studies have shown related males to occur on leks no more than expected by chance. Additionally, evidence supporting the proposed mechanism is mixed; by joining a lek, males do not always increase the female visitation rate on a per-capita basis. The prairie mole cricket Gryllotalpa major is a lekking cricket in which male relatives advertise in close proximity. We reject the Kokko–Lindstrom hypothesis for this species because G. major females do not preferentially visit larger leks. Interestingly, more females visited smaller leks, where the presence of larger, more highly related males suggest reduced levels of local competition. Although the mechanism continues to be explored, these results provide an alternative inclusive fitness scenario to consider for lekking species—the existence of kin benefits between related neighbors rather than spread across the lek as a whole.